The Royal Proclamation of 1763 (Canada Watch, 2013)
George III. (1763). London: Printed by Mark Baskett, Printer to the King’s most Excellent Majesty; and by the Assigns of Robert Baskett. http://www.aadnc-aandcgc.ca/eng/1370355181092/1370355203645Miller, J.R. (2009). Compact, Contract, Covenant: Aboriginal Treaty-Making in Canada.Toronto: University of Toronto Press.